Model Pembelajaran Problem-Based Learning Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa: Sebuah Meta Analisis Perbandingan Pelajaran Eksak dan Non Eksak - Azmiatun Solehah; Vera Mandailina; Mahsup Mahsup; Syaharuddin Syaharuddin; Abdillah Abdillah (Universitas Negeri Gorontalo, 2023)
The purpose of this study is to analyze more deeply the effectiveness of problem-based learning (PBL) in improving students' critical thinking skills, especially in exact and non-exact subject areas. Data were synthesized from 30 relevant research results over the past 10 years, then analyzed using meta-analysis through effect size (ES) and standard error (SE) values to see the summary effect size. The results of the analysis using JASP software showed that the level of effectiveness in exact and non-exact subjects was 65% and 92%, respectively. This shows that the effectiveness of the PBL learning model in improving students' critical thinking skills is higher in non-exact materials. Furthermore, the results of the analysis based on the level of education show that at the high school level has an effect of 89%, this value is higher than the elementary level of 69% and junior high school of 83%. Thus, in the future, the application of the PBL model is highly emphasized to be implemented at the high school level for non-exact subjects.